Exercise training modulates functional sympatholysis and α‐adrenergic vasoconstrictor responsiveness in hypertensive and normotensive individuals. (30th June 2014) - Mortensen, Stefan P.; Nyberg, Michael; Gliemann, Lasse; Thaning, Pia; Saltin, Bengt; Hellsten, Ylva
Abstract : Key points: Essential hypertension is linked to an increased sympathetic vasoconstrictor activity and reduced tissue perfusion. Exercise training can improve the ability to override sympathetic vasoconstrictor activity. Here we show that 8 weeks of exercise training reduces the vasoconstrictor response to sympathetic nerve activity (induced by tyramine) and improves the ability to override sympathetic vasoconstrictor activity. We found no difference in the ability to override sympathetic vasoconstrictor activity during exercise, the reduction in blood flow in response to increases in sympathetic nerve activity or the hyperaemic response to infused ATP between normo‐ and hypertensive subjects. These results help us to better understand how exercise training can reduce blood pressure and improve tissue perfusion. Abstract: Essential hypertension is linked to an increased sympathetic vasoconstrictor activity and reduced tissue perfusion. We investigated the role of exercise training on functional sympatholysis and postjunctional α‐adrenergic responsiveness in individuals with essential hypertension. Leg haemodynamics were measured before and after 8 weeks of aerobic training (3–4 times per week) in eight hypertensive (47 ± 2 years) and eight normotensive untrained individuals (46 ± 1 years) during arterial tyramine infusion, arterial ATP infusion and/or one‐legged knee extensions. Before training, exercise hyperaemia and leg vascular conductance (LVC) were lower in the hypertensive individuals ( P  < 0.05) and tyramine lowered exercise hyperaemia and LVC in both groups ( P  < 0.05). Training lowered blood pressure in the hypertensive individuals ( P  < 0.05) and exercise hyperaemia was similar to the normotensive individuals in the trained state. After training, tyramine did not reduce exercise hyperaemia or LVC in either group. When tyramine was infused at rest, the reduction in blood flow and LVC was similar between groups, but exercise training lowered the magnitude of the reduction in blood flow and LVC ( P  < 0.05). There was no difference in the vasodilatory response to infused ATP or in muscle P2Y2 receptor content between the groups before and after training. However, training lowered the vasodilatory response to ATP and increased skeletal muscle P2Y2 receptor content in both groups ( P  < 0.05). These results demonstrate that exercise training improves functional sympatholysis and reduces postjunctional α‐adrenergic responsiveness in both normo‐ and hypertensive individuals. The ability for functional sympatholysis and the vasodilator and sympatholytic effect of intravascular ATP appear not to be altered in essential hypertension.